Comparative analysis of the bronchoalveolar microbiome in Portuguese patients with different chronic lung disorders - Seixas, Susana (2021)
Funding Information: We would like to thank all patients for donating their samples and for collaborating in this study. IPATIMUP integrates the i3S Research Unit, which is partially supported by the Portuguese Foundation for Science and Technology (FCT). This work was supported by Norte Portugal Regional Programme (NORTE 2020), under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund (FEDER)— project NORTE-01-0145-FEDER-000029. This work was also financed by FEDER funds through COMPETE 2020 (Operacional Programme for Competitiveness and Internationalization— POCI) and by private funds through the Young Investigator Prize Francisco Augusto da Fonseca Dias and Maria José Melenas da Fonseca Dias to P.I.M. FCT supports P.I.M. through a post-doctoral fellowship (SFRH/BPD/120777/2016), financed by the Portuguese State Budget of the Ministry for Science, Technology and High Education and from the European Social Fund (Programa Operacional do Capital Humano—POCH). M.P-L was partially supported by FCT under the Programa Operacional Potencial Humano—Quadro de Referência Estratégico Nacional funds from the European Social Fund and Portuguese State Budget of the Ministry for Science, Technology and High Education (IF/00764/2013; RX: IF/00359/2015). Publisher Copyright: © 2021, The Author(s).